Repetitive transcranial magnetic stimulation for apathy in patients with neurodegenerative conditions, cognitive impairment, stroke, and traumatic brain injury: a systematic review - Espiritu, Adrian I.; Hara, Takatoshi; Tolledo, Joy Kirsten; Blair, Mervin; Burhan, Amer M. (Frontiers in Psychiatry, 2023)
We aimed to determine the effects and tolerability of repetitive transcranial magnetic stimulation (rTMS) on apathy in patients with neurodegenerative conditions, mild cognitive impairment (MCI), stroke, and traumatic brain injury (TBI) via systematic review.We conducted a systematic search in major electronic health databases, including PubMed, Scopus, and PsycINFO, covering the period from inception to June 2023. Comparative clinical trials and cohort studies, and studies with before-after designs were considered for inclusion. We used the Cochrane Risk of Bias and the National Institutes of Health (NIH) tools to assess methodological quality.Out of 258 records identified, 14 studies met our eligibility criteria (11 randomized controlled trials (RCT) and 3 studies utilized before-and-after designs) with a total of 418 patients (overall female-tomale ratio 1:1.17) included in the review. The overall methodological quality of the included studies was assessed to be fair to good. The stimulation parameters used varied considerably across the studies. The summary findings of our review indicate the following observations on the effects of rTMS on apathy: (1) the results of all included studies in Alzheimer's disease investigating the effects of rTMS on apathy have consistently shown a positive impact on apathy; (2) the majority of studies conducted in Parkinson's disease have not found statistically significant results; (3) a singleThis is a provisional file, not the final typeset article study (RCT) on patients with primary progressive aphasia demonstrated significant beneficial effects of rTMS on apathy; (4) the trials conducted on individuals with MCI yielded varying conclusions; (5) one study (RCT) in chronic stroke suggested that rTMS might have the potential to improve apathy; (6) one study conducted on individuals with mild TBI did not find a significant favourable association on apathy; and (7) the use of different rTMS protocols on the populations described is generally safe.The feasibility of utilizing rTMS as a treatment for apathy has been suggested in this review. Overall, limited evidence suggests that rTMS intervention may have the potential to modify apathy among patients with AD, PPA, MCI and chronic stroke, but less so in PD and mild TBI. These findings require confirmation by larger, well-designed clinical trials.